Eye movement desensitization and reprocessing (EMDR) therapy - Russell, Mark C. (Mark Charles), 1960-; Shapiro, Francine (Theories of psychotherapy series., 2022)
"Eye Movement Desensitization and Reprocessing therapy (EMDR) is a unique, empirically validated approach that is recommended by the World Health Organization as a 'first line treatment for post traumatic stress disorder in adults.' EMDR therapy emphasizes working with imagery, cognitions, emotions, somatic sensations, and behavior linked to a disturbing memory, as well as attending to past, current, and future-oriented experiential contributors. Unlike many psychotherapeutic treatments, EMDR does not require prolonged exposure, the direct challenging of beliefs, or numerous sessions to achieve results. In this book, Dr. Shapiro, the originator of this approach, and Dr. Russell, her longtime colleague and collaborator, describe their work and the significant controversy that attended its rise due to EMDR's challenging of traditional cognitive behavioral approaches to psychotherapy and mechanisms of change. The authors describe the theory of EMDR, provide the complete EMDR therapeutic protocol, the evidence base that supports it, and examine practical issues and common challenges related to implementing EMDR in clinical practice"--